EFISIENSI DAN INOVASI PEMANFAATAN LIMBAH TULANG IKAN TUNA PADA KELOMPOK POKLAHSAR BUBULLA KELURAHAN JAMBULA KOTA TERNATE - Wulandari, Tri Laela; Adriani, Adriani; Nurjannah, Siti; Disnawati, Disnawati (Jurnal Abdi Insani, 2025)
Tuna fisheries are a vital sector in Ternate City; however, the processing of tuna produces large amounts of bone waste that remain underutilized. This waste poses environmental risks while representing a lost economic opportunity. The Poklahsar Bubulla group currently processes tuna meat into shredded fish products, while the bones are discarded. Therefore, an outreach program was conducted to improve community knowledge on efficient and innovative utilization of tuna bone waste. The activity was carried out on August 2025, in Jambula Village, Ternate City, involving 10 Poklahsar Bubulla members. The method applied was interactive counseling through presentations, group discussions, and evaluation using pre-test and post-test. The results showed a significant improvement in participants’ understanding, with the average pre-test score of 63.6% increasing to 91.0% in the post-test, resulting in an N-gain of 0.75 (high category). Participants responded positively, demonstrating enthusiasm in discussions and gaining new awareness of the economic and environmental potential of tuna bone waste utilization. In conclusion, this counseling activity effectively enhanced knowledge and motivation among fish processors to develop innovative uses of tuna bone waste.